An Update on the Efficacy and Functionality of Probiotics for the Treatment of Non-Alcoholic Fatty Liver Disease. (May 2021) - Yao, Mingfei; Qv, Lingling; Lu, Yanmeng; Wang, Baohong; Berglund, Björn; Li, Lanjuan
Abstract: Non-alcoholic fatty liver disease (NAFLD), which has a global prevalence of 20%–33%, has become the main cause of chronic liver disease. Except for lifestyle medication, no definitive medical treatment has been established so far, making it urgent to find effective strategies for the treatment of NAFLD. With the identification of the significant role played by the gut microbiota in the pathogenesis of NAFLD, studies on probiotics for the prevention and treatment of NAFLD are increasing in number. Bacteria from the Bifidobacterium and Lactobacillus genera constitute the most widely used traditional probiotics. More recently, emerging next-generation probiotics (NGPs) such as Akkermansia muciniphila and Faecalibacterium prausnitzii have also gained attention due to their potential as therapeutic options for the treatment of NAFLD. This review provides an overview of the effects of oral administration of traditional probiotics and NGPs on the development and progress of NAFLD. The mechanisms by which probiotics directly or indirectly affect the disease are illustrated, based on the most recent animal and clinical studies. Although numerous studies have been published on this topic, further research is required to comprehensively understand the specific underlying mechanisms among probiotics, gut microbiota, and NAFLD, and additional large-scale clinical trials are required to evaluate the therapeutic efficacy of probiotics for the treatment of NAFLD, as well as the safety of probiotics in the human body.